Genetic and clinics in terms of Down syndrome - Özbey, Ülkü; Yüce, Hüseyin (My University, 2007)
Trisomies occur in the result of "meiotic non-disjunction" during gametogenesis. In humans, trizomi 21 or Down syndrome (DS) is the best known and the most seen trisomies. Trismoy 21 is one of the most common chromosomal abnormalities with mental retardation (MR) and characteristic physicol symptoms in humans. DS is characterized by moderate MR and a variety of abnormalities involving multiple organ systems. Trisomy 21 occurs in 1/750 live births. It is caused by triplicate state (trisomy) of all or a critical portion of chromosome 21. Individuals with DS often have specific major congenital malformations,. Leukemia (both ALL and AML) and leukemoid reactions show increased incidence in Down syndrome. Trisomy 21 etiology, basic mechanisms of nondisjunction are still poorly understood. In individuals with DS, treatment and identification of medical disorders decline in their function will prevent morbidity. In this review, risk factors associated with this type of chromosome error occurring in oogenesis and spermatogenesis are discussed based on the literature. Parental karyotypes, family history and parental ages has helped us greatly in offering genetic counseling, prenatal diagnosis and estimating the risk for the next conception.
Genetik ve klinik açidan Down sendromu
Keywords: amniocentesis; chorion villus sampling; Down syndrome; family history; fetoscopy; genetic counseling; genetics; human; incidence; karyotype; oocyte development; parental age; review; risk factor; spermatogenesis